PENGARUH SUBSTITUSI TEPUNG KEDELAI DENGAN TEPUNG BIJI KARET PADA PAKAN BUATAN TERHADAP PERTUMBUHAN IKAN BAWAL AIR TAWAR (Colossoma macropomum) - Limin Santoso; Hery Agusmansyah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
Tambaqui fish much culture in Indonesia because have a fast growth andresistant to diseases. The latest aquaculturist problem is the high price of fishfeed. One of materials used in fish feed formulation is soybean meal which is veryexpensive, because it is an import basic commodity. One of alternative toovercome these problems is to replace with local raw materials such as rubberseed meal with a potentially lower the cost of feed production. The research tostudy the effect of rubber seed meal as a substitution of soy bean meal. Theresearch was conducted by using completed random design with six treatment andthree replications that which had different level comparation of soy bean meal andrubber seed meal, as follows A (45% : 0%); B (40% : 5%); C (30% : 15%); D(20% : 25%); E (10% : 35%) and F (0% : 45%). The data was analysed by Anovaand continued with least significantly different test (P>0,05). The rubber seedmeal as a substitution of soy bean meal were not significantly different on thegrowth rate. The rubber seed meal 5% it can be concluded, substitution of soybean meal 40% with 5% rubber as a substitute for soybean meal in feed to a hadthe growth (9,9 g) were not significantly different (P>0,05) with the used of feedis no substitution of rubber seed meal (10,2 g) of tambaqui fish. substitution ofsoy bean meal with rubber seed meal at level 5% can be used as feed formulationof tambaqui fish.